A Capacitor‐type Faradaic Junction for Direct Solar Energy Conversion and Storage. Issue 3 (16th November 2020) - Wang, Pin; Chen, Xiangtian; Sun, Gengzhi; Wang, Cheng; Luo, Jun; Yang, Liuqing; Lv, Jun; Yao, Yingfang; Luo, Wenjun; Zou, Zhigang
Abstract: Two‐electrode solar rechargeable devices trigger intense attention due to their potential applications in solar energy conversion and storage. However, interface energy barriers lead to severe loss of output voltage and negligible dark discharge current. Therefore, external biases are required for dark discharge in these devices, limiting their practical applications. Herein, we report a new two‐electrode device of Si/WO3 /H2 SO4(aq) /C that can work without bias. The device has the highest dark output power among all of the two‐electrode solar rechargeable devices. The device based on a Si/WO3 junction indicates photoinduced adjustable interface barrier height during charge transfer, which can overcome the energy barrier and realize dark discharge without bias. Owing to the interface characteristics, the Si/WO3 is designated as a capacitor‐type Faradaic junction. Abstract : A Faradaic junction with adjustable barrier height is used for a facile two‐electrode solar rechargeable device under zero bias.